Tumour-associated macrophages: versatile players in the tumour microenvironment - Ji, Zoey Zeyuan; Chan, Max Kam-Kwan; Chan, Alex Siu-Wing; Leung, Kam-Tong; Jiang, Xiaohua; To, Ka-Fai; Wu, Yi; Tang, Patrick Ming-Kuen (Frontiers in Cell and Developmental Biology, 2023)
Tumour-Associated Macrophages (TAMs) are one of the pivotal components of the tumour microenvironment. Their roles in the cancer immunity are complicated, both pro-tumour and anti-cancer activities are reported, including not only angiogenesis, extracellular matrix remodeling, immunosuppression, drug resistance but also phagocytosis and tumour regression.Interestingly, TAMs are highly dynamic and versatile in solid tumours. They can show anticancer or pro-tumour activities, and interplay between the tumour microenvironment and cancer stem cells and under specific conditions. In addition to the classic M1/M2 phenotypes, a number of novel dedifferentiation phenomena of TAMs are discovered due to the advanced single-cell technology, e.g., macrophage-myofibroblast transition (MMT) and macrophageneuron transition (MNT). More importantly, emerging information demonstrated the potential of TAMs on cancer immunotherapy, suggesting by the therapeutic efficiency of the checkpoint inhibitors and chimeric antigen receptor engineered cells based on macrophages. Here, we summarized the latest discoveries of TAMs from basic and translational research and discussed their clinical relevance and therapeutic potential for solid cancers.